Evolution of rheological parameters and apparent molecular weight distribution in the bitumen from reclaimed asphalt with rejuvenation and re-ageing. (1st August 2022) - Bocci, Edoardo; Prosperi, Emiliano; Marsac, Paul
Abstract : The paper aims at analysing the evolution of the rheological behaviour of the bitumen extracted from reclaimed asphalt (RA) with rejuvenation (blending of virgin and RA bitumen, with addition of a rejuvenator) and re-ageing. The complex modulus of the binders was measured through a DSR device, while RTFOT and PAV protocols were followed to reproduce the bitumen ageing. Three rheological models were used in order to study the evolution of their parameters in the various steps. In addition, the apparent molecular weight distribution (AMWD), determined through δ -method, was analysed. The results showed that the rejuvenator could reduce RA bitumen stiffness but had low effect on the phase angle. After long-term re-ageing, the rejuvenated RA bitumen showed comparable rheological behaviour with respect to the bitumen initially recovered from RA. However, the AMWD analysis showed that the rejuvenator did not adequately disrupt the asphaltene clusters in the aged bitumen.